2005
DOI: 10.1016/j.biomaterials.2005.04.017
|View full text |Cite
|
Sign up to set email alerts
|

The cellular response to transglutaminase-cross-linked collagen

Abstract: Collagen, type I, is a highly abundant natural protein material which has been cross-linked by a variety of methods including chemical agents, physical heating and UV irradiation with the aim of enhancing its physical characteristics such as mechanical strength, thermal stability, resistance to proteolytic breakdown, thus increasing its overall biocompatibility. However, in view of the toxicity of residual cross-linking agents, or impracticability at large scales, it would be more useful if the collagen could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
161
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 192 publications
(168 citation statements)
references
References 41 publications
5
161
1
1
Order By: Relevance
“…One of the important functions of TG2 pertains to its role in the extracellular environment where it may influence both cell adhesion (Akimov et al 2000;Telci et al 2008;Verderio et al 2003) and matrix accumulation/stability (Akimov and Belkin 2001;Chau et al 2005). In all TG2-transfected clones, TG2 was found at the cell surface, but in keeping with our earlier studies (Balklava et al 2002;Gaudry et al 1999), only in the clones transfected with the active wild type enzyme was it found deposited in the extracellular matrix (ECM).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…One of the important functions of TG2 pertains to its role in the extracellular environment where it may influence both cell adhesion (Akimov et al 2000;Telci et al 2008;Verderio et al 2003) and matrix accumulation/stability (Akimov and Belkin 2001;Chau et al 2005). In all TG2-transfected clones, TG2 was found at the cell surface, but in keeping with our earlier studies (Balklava et al 2002;Gaudry et al 1999), only in the clones transfected with the active wild type enzyme was it found deposited in the extracellular matrix (ECM).…”
Section: Discussionsupporting
confidence: 66%
“…In the extracellular environment, TG2 can also function through its Ca 2? -activated transamidating activity to increase the rate of deposition of ECM proteins such as FN and collagen I (Shweke et al 2008;Verderio et al 1999;Yuan et al 2007), leading to accumulation and changes in the ECM influencing both cell adhesion and differentiation (Chau et al 2005;Johnson et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Our initial objective in this paper was, therefore, to identify the HSPG involved in this interaction with TG-FN and to determine whether this interaction is mediated directly via binding of the HSPG to TG2 as TG2 is known to have a high affinity for heparin (15). First we show that CHO-K1 cells deficient in synthesis of HS chains did not attach or spread on TG-FN in an RGD-independent manner, confirming the importance of HS chains in this process.…”
Section: Discussionmentioning
confidence: 99%
“…TG2 can enhance the cell attachment and spreading of a number of different cell types through the modification of ECM proteins by their cross-linking (15,16). However, recent reports also describe a non-transamidating mechanism whereby TG2 acts as a novel cell adhesion protein (6,17) thought to involve direct interaction with a variety of integrin receptors.…”
mentioning
confidence: 99%
“…Infusions of factor XIII to reduce bleeding during cardiopulmonary bypass surgery has been discussed. Transglutaminase-modified matrices could be used to improved physical and biological properties or to incorporate specific agents into engineered tissues (188)(189)(190).…”
Section: Diagnostic and Therapeutic Implications Of Transglutaminasesmentioning
confidence: 99%